The adjustment of Moldova's competition law to European Union competition law - Dumitriţa Bologan (Europa-Kolleg Hamburg, Institute for European Integration, 2015)
This paper explores the historical background of the political and economic relations between the Republic of Moldova and the European Union, presenting an overview of relevant documents such as the Partnership and Cooperation Agreement and the Association Agreement. Special emphasis is put on the development of competition law in Moldova as one of the main instruments for ensuring the function of a market economy. In this context, the paper also addresses the process of adjustment of Moldova's relevant legislation to the European Union competition law, describing the range of legal instruments and institutions involved in this process and the monitoring thereof by the European Union.
Keywords: 320; European integration; Partnership and cooperation agreement; Association agreement; European competition law; Moldavian competition law; Adjustment of competition rules; Neighbor policy